Daikenchuto improves methotrexate-induced chronic small intestinal mucositis by promoting angiogenesis - Li, Peilin; Inoue, Yusuke; Sadatomi, Daichi; Mogami, Sachiko; Miyamoto, Daisuke; Adachi, Toshiyuki; Adachi, Tomohiko; Soyama, Akihiko; Kanetaka, Kengo; Gu, Weili; Eguchi, Susumu (Frontiers in Pharmacology, 2025)
AimChronic small-intestinal mucositis (CIM) is a severe gastrointestinal complication that has limited treatment options. This study investigated the potential therapeutic effects of Daikenchuto (DKT), a traditional medicine, on mitigating methotrexate (MTX)-induced CIM in rats.MethodsMale Sprague-Dawley rats were assigned to four groups: control, MTX, DKT-MTX, and DKT. CIM was induced by intraperitoneal administration of MTX (10 mg/kg every 6 days), while DKT (2.7% wt/wt) was orally administered via feed. The surviving rats were euthanized on day 60. Rat intestinal epithelial cells (IEC-6) were used to examine DKT’s cytoprotective effects in vitro.ResultsDKT treatment improved survival, reduced gastrointestinal symptoms, and alleviated histological damage, including villus atrophy and crypt hyperplasia. DKT restored mucosal integrity by enhancing the expression of tight junction proteins (CLDN-3) and nutrient transporters (B0,+AT, EAAT3), and by reducing oxidative stress and epithelial cell death. Furthermore, DKT promoted mucosal angiogenesis, as evidenced by increased expression of CD34, VEGFR2, and VEGFA in both tissues and cells. qRT-PCR confirmed upregulation of genes associated with angiogenesis, barrier repair, and mucosal regeneration.ConclusionDKT exerts protective effects against MTX-induced CIM by enhancing angiogenesis, promoting epithelial regeneration, and restoring mucosal barrier function. These findings suggest DKT as a promising adjunctive therapy for managing chronic intestinal toxicity induced by chemotherapy.